Financial Capacity for Sustainable Growth of Listed Agricultural Enterprises in Vietnam - Lan , Tran Thi (International Journal of Accounting and Economics Studies, 2026)
In the context of Vietnam facing common challenges in both global and domestic economies, achieving sustainable development for businesses has become a pressing concern for managers and investors. This article selects listed companies in the ‎agricultural sector for analysis and evaluation. Agricultural companies are an indispensable part of the farm modernization process, ‎playing the role of a bridge between farmers and the consumer market. However, agrarian companies show low sustainable growth. The ‎difficulty is basically financial problems, especially financial capacity. Based on the sustainable growth models proposed by scientists ‎Higgin (1977) [1] and Van Horne (1987) [2], the article evaluates the impact of financial capacity on the sustainable growth of 23 agricultural ‎companies listed on the Vietnam Stock Exchange, secondary data collection period from 2017 - 2024. By using quantitative modeling ‎research methods of OLS, FEM, REM, and GLS models. There is evidence that financial capacity has a strong impact on the growth of ‎agricultural companies, with a coefficient of determination (R2) of 0.528 in the entire sample. Profitability is an important factor that ‎positively affects the sustainable growth of listed agricultural companies. Meanwhile, the factor of operating efficiency, measured by ‎operating expenses over total sales and service revenue, has a negative impact. The new findings show that the factors of enterprise size, ‎level of financial leverage, investment project portfolio, and payment capacity are not statistically significant for the model. Finally, the paper ‎gives some recommendations for improving the financial capacity associated with the sustainable growth of agricultural companies‎.
Keywords: Sustainable Growth; Agricultural Enterprises; Enterprise Size; Profitability; Operating Efficiency; Financial Leverage